2008
DOI: 10.1002/micr.20563
|View full text |Cite
|
Sign up to set email alerts
|

Muscle sparing‐2 transverse rectus abdominis musculocutaneous flap for breast reconstruction: A comparison with deep inferior epigastric perforator flap

Abstract: Breast reconstruction using free transverse rectus abdominis musculocutaneous (TRAM) flap can be divided into 4 muscle-sparing (MS) types: conventional TRAM flap containing full width muscle as MS-0, while deep inferior epigastric perforator (DIEP) flap containing absolutely no muscle as MS-3. We include only the muscle portion between the medial row and lateral row perforator vessels in TRAM flap, which is designated as MS-2. Between October 1999 and April 2006, the same surgeon performed 82 breast constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Only a portion of the fatty layer of the flap is fed in a vertical direction from vessels derived from the subdermal and fascial vascular networks, and hence, the adipose layer might be the most peripheral site of blood circulation in the TRAM flap. 13,33,42 On the other hand, the division of the flap to different zones is probably not exactly similar in different studies.…”
Section: Discussionmentioning
confidence: 91%
“…Only a portion of the fatty layer of the flap is fed in a vertical direction from vessels derived from the subdermal and fascial vascular networks, and hence, the adipose layer might be the most peripheral site of blood circulation in the TRAM flap. 13,33,42 On the other hand, the division of the flap to different zones is probably not exactly similar in different studies.…”
Section: Discussionmentioning
confidence: 91%
“…23 These studies were also included for the summarization of pooled complication rates except for 1 with fewer than 10 patients in each subgroup. The other 7 studies 9,19,30-34 (2 presenting data only for obese patients 6,9 and 5, only for nonobese patients [30][31][32][33][34] were use) for the pooled analysis (Tables 2 and 3). As a result, a total of 14 studies were suitable for the calculation of pooled complication rates for muscle-conserving abdominal flaps.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Reports have described abdominal wall hernia and bulge rates as high as 62% for p-TRAM 3 , 27% for f-TRAM 4 , 11% for msf-TRAM 5 , and 10% for DIEP flaps. 6,7 While advances in abdominal wall closure techniques may minimize hernia and bulge complications, these are unlikely to decrease abdominal wall weakness and a patient’s ability to conduct activities of daily life without discomfort. 6 Multiple studies evaluating objective abdominal wall strength with functional dynamometry have demonstrated significant differences between different types of flaps.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 While advances in abdominal wall closure techniques may minimize hernia and bulge complications, these are unlikely to decrease abdominal wall weakness and a patient’s ability to conduct activities of daily life without discomfort. 6 Multiple studies evaluating objective abdominal wall strength with functional dynamometry have demonstrated significant differences between different types of flaps. 8,9,10,11,12,13 In these studies, patients with f-TRAM and p-TRAM reconstruction have been found to have more abdominal wall weakness relative to msf-TRAM and DIEP groups.…”
Section: Introductionmentioning
confidence: 99%